Investigating the link between teachers' perceptions of 21st century skills efficiency and students' perceptions of learning experience: Mediating role of teacher's self-efficacy - Ahmet Kara; Şengül Saime Anagün; Şerife Dilek Boyacı; Serhat Yaşar (Journal of Pedagogical Research, 2022)
This study aimed to put forward the mediating role of teacher self-efficacy in the relationship between students' perceptions of learning experience and teachers' perceptions of 21st century skills efficacy. Participants of the research consisted of two groups. First group is 262 teachers and the second group is 622 primary school students. Data were collected with the Learning Experience Perceptions Scale (LEPS), Turkish version of the Teachers' Sense of Efficacy Scale (TTSES) and 21st Century Skills and Competences Scale (21stCSCS). The data were analysed with Two-Stage Structural Equation Modeling (SEM). The research results revealed that teacher self-efficacy has a full mediating effect between students' perceptions of learning experience and teachers' perceptions of 21st century skills competence.